LEARNING OBSTACLE MATERI PERSAMAAN GARIS LURUS DITINJAU DARI HEURISTIK POLYA - Citra Aditia Rahayu; Nelly Fitriani; Wahyu Setiawan (IKIP Siliwangi, 2023)
The purpose of this study was to analyze students' learning difficulties in independent learning. The method used is descriptive qualitative method. An example of this research is SMA Class VIII-A. Dharma Kartini Simahi has 28 students. Purposive sampling method. The data collected is in the form of a 3-point assessment tool with specific questions about students' ability to follow the Polya heuristic steps. Methods of data analysis include data management through objective definitions and qualitative analysis of student achievement test results. The learning barriers found in this study are ontogenic barriers (conceptual errors), epistemological barriers (practical problems) and educational barriers (teaching problems). The results showed that 43% of students were able to explain the problem and the lowest score in solving the problem was 14% of the total.